Fish Farming Analysis System Of Culture Cage Floating (KJA) In Sengai Paku Village, Sub-District Of Kampar Kiri, Kampar District, Riau Province - Sasmi, Hesti; Hendri, Ridar; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Research on the business of cultivating system analysis fish keramba buoyant net carried out in february 2015 spikes in the village the kecamatan kampar left kabupaten Kampar provinsi riau .This study aims to to see how investment large kicked out at a venture the cultivation of fish, to see how large net income obtained cultivator of the and to know business feasibility in keramba a net buoyant. Based on the results of research the average investment and production costs that kicked out to venture baung 20.492.500 fish as much as rp, while to venture nila fish who kicked out as much as rp .18.817.000 , the average income that net in can be of an effort as much as rp 5.352.300 baung fish, while to venture nila fish as much as rp. And the average 926.467 feasibility ( rcr) effort the cultivation of fish baung of 1.369 and nila fish of 1.067.keywords: the cultivation of baung and tilapia, worthiness of business investment